2002
DOI: 10.1080/02626660209492960
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Sahelian annual rainfall index from 1896 to 2000; the drought continues

Abstract: Since 1970 the West African Sahel has experienced a significant drought which, according to some authors, corresponds to a discontinuity (abrupt change) in the rainfall series. An annual rainfall index was calculated over the period from 1896 to 2000, with a selection of 21 synoptic stations updated regularly by the Agrhymet Regional Centre in Niamey. Several statistical analyses of the index confirmed the previous descriptions, particularly the significance of the drought since 1970 and a nonstationarity, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 235 publications
(136 citation statements)
references
References 13 publications
9
112
0
4
Order By: Relevance
“…Lamb and Peppler, 1992;Nicholson et al, 2000;L'Hôte et al, 2002). For example, Lamb's index (Tarhule and Lamb, 2003;also see Figure 3(b)) has used the same 20 Sahelian stations since it was first developed in the mid-1970s; exactly half of those stations are west/east of the 6°W boundary used by Chappell and Agnew (2004), and only 13 station-years out of 1220 during 1941-2001 had missing data.…”
Section: Flaws In Chappell and Agnew (2004)mentioning
confidence: 99%
See 2 more Smart Citations
“…Lamb and Peppler, 1992;Nicholson et al, 2000;L'Hôte et al, 2002). For example, Lamb's index (Tarhule and Lamb, 2003;also see Figure 3(b)) has used the same 20 Sahelian stations since it was first developed in the mid-1970s; exactly half of those stations are west/east of the 6°W boundary used by Chappell and Agnew (2004), and only 13 station-years out of 1220 during 1941-2001 had missing data.…”
Section: Flaws In Chappell and Agnew (2004)mentioning
confidence: 99%
“…However, one can easily verify whether the decreasing trend in the number of stations is a cause of the trend in the Sahel regional rainfall time series by, for example, looking at trends at fixed stations (e.g. Nicholson et al, 2000;L'Hôte et al 2002), or analysing a subset of fixed stations with nearly continuous rainfall data, as we do here.…”
Section: Effects Of Changing Station Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to contradictory results from climate trend studies at local and subregional scales. For instance, following the 1990s' report of the Sahelian drought (Sivakumar 1992;Le Barbé and Lebel 1997), several studies considered it either ended in the 1990s (Ozer et al 2003), continued (Hulme 2001;L'Hote et al 2002;Dai et al 2004) or even was simply an artifact of changing station networks (Chappell and Agnew 2008). The recent discovery of a precipitation gradient from eastern to western Sahel ) in addition to the north-south Inter Tropical Convergence Zone (ITCZ) influence on rainfall distribution is also a factor of importance for reliable hydrological predictions in West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Maps depicting the rainfall patterns and trends for the periods 1940/1970 and 1971/1995 are drawn, as several works have given 1970 as the beginning of the rainfall deficit in West Africa on average (Mahe et al, 2001;L'Hote et al, 2002;Paturel et al, 2003b), as shown in the rainfall dataset plot in Figure 4, with the rupture in 1970 according to the different detection tests available in the Khronostat software (Lubes-Niel et al, 1998). The rainfall and runoff changes in 1970 are very well marked over the Bani River (Mahe et al, 2000), and on a larger scale for other rivers of West Africa (Mahe and Olivry, 1999) using the same software.…”
Section: Resultsmentioning
confidence: 99%